Investigating the Quality of Milk using Spectrometry Technique and Scattering Theory - Kamil Ν. Α. Ι. Μ.; Nor’aini, Z. S.; Wan Ismail, W. Z.; Balakrishnan, S. R.; Jamaludin, J.; Ismail, I.; Sahrim, M. (Engineering, Technology & Applied Science Research, 2021)
Milk is a dairy product that contains dissolved proteins, carbohydrates, fat, and many minerals. Milk enhances body growth and provides vital energy and fatty acids. Milk can turn bad after being kept at room temperature for several days. The endurance of milk could depend on its fat and protein composition. Our work aims to compare the quality of milk after being kept at room temperature for several days using spectroscopy methods. Modeling based on scattering theory is also provided to compare the light propagation in milk, water, and air. A VIS-NIR spectrometer was used to observe the light absorption, transmission, and reflectance whereas a modeling approach was applied to study the scattering, absorption, and extinction efficiencies. The milk samples consist of full cream milk kept at room temperature for 8 days, 11 days, 14 days, and 17 days. The results show that milk without fermentation has higher light absorbance and lower transmission compared to milk with fermentation, due to changes in milk composition after the fermentation process. Milk scatters more light compared to water and air due to its fat globule and protein ingredients. The output of this study can be used as a reference for studies involving bacteria or microorganisms in milk. It also can be used to compare the quality of milk with and without air exposure.